Campylobacter enteritis in the Arabian Gulf - Abiola C. Senok; Giuseppe A. Botta (Journal of Infection in Developing Countries)
Diarrhoea illnesses constitute a common cause of morbidity and mortality worldwide. In recent years, Campylobacter spp. has been recognized as the leading cause of bacterial enteritis in both developed and developing countries. The biology of Campylobacters as well as the mechanism by which they cause disease is yet to be fully explained. In addition, non-availability of fast and reliable diagnostic methodology and the growing trend of antibiotic resistance continue to pose significant challenges. The absence of national surveillance programs for campylobacteriosis, particularly in developing countries, makes it difficult to give an accurate picture of the true infection prevalence and the molecular epidemiology of isolates circulating in the populations, a situation which had hitherto existed in the Arabian Gulf region. However, in recent years, emerging data from studies in the Arabian Gulf region has not only enhanced our understanding of the epidemiology of Campylobacter both in humans and poultry in the region, but has also contributed to the overall understanding of the mechanism of Campylobacter enteritis, antibiotic resistance, and improved diagnostic approaches. In this review, we examine these emerging data from the Arabian Gulf region.